Digital Trade Finance Transformation and Sustainable Marketing Strategies: A Literature Review - Indrianti, Marini Astari; Nurdin, Asep; Perdhana, Mirwan Surya (LifeSciFi, 2025)
Digital transformation is reshaping the banking sector, particularly in trade finance, improving operational efficiency and providing better solutions for international transactions. Bank Rakyat Indonesia (BRI) developed the